Novel biflavonoids from Cephalotaxus oliveri Mast. (April 2018) - Ren, Dai; Meng, Fan-Cheng; Liu, Hui; Xiao, Tong; Lu, Jin-Jian; Lin, Li-Gen; Chen, Xiu-Ping; Zhang, Qing-Wen
Graphical abstract: Three new biflavonoids, including umcephabiflovins A (1 ) and B (2 ) as well as S -taiwanhomoflavone-B (3 ), together with fourteen known compounds (4–17 ) were isolated from Cephalotaxus oliveri Mast. The flavonoids showed α-glucosidase inhibitory effects. Highlights: Three new biflavonoids were isolated from Cephalotaxus oliveri . Seven known flavonoids and seven alkaloids were also isolated. Their structures were determined by spectroscopic analysis. Their absolute configurations were elucidated through CD spectra. The flavonoids showed α-glucosidase inhibitory effects. Abstract: Three new biflavonoids, umcephabiflovin A (1 ), umcephabiflovin B (2 ), and S -taiwanhomoflavone-B (3 ), together with seven known flavonoids (4–10 ) and seven known alkaloids (11 –17 ), were isolated from the twigs of Cephalotaxus oliveri Mast. The flavonoids were found to inhibit α-glucosidase activity.